Association of spontaneous cerebrospinal fluid rhinorrhea with transverse venous sinus stenosis: a retrospective matched case‐control study. Issue 12 (23rd July 2020) - Bedarida, Vincent; Labeyrie, Marc‐Antoine; Eliezer, Michael; Saint‐Maurice, Jean‐Pierre; Jourdaine, Clément; Gargalas, Sergios; Herman, Philippe; Houdart, Emmanuel; Verillaud, Benjamin
Abstract : Background: A significant proportion of spontaneous cerebrospinal fluid (sCSF) leaks are associated with idiopathic intracranial hypertension (IIH). The aim of this study was to assess the association between sCSF rhinorrhea and transverse venous sinus stenosis (VSS), a feature commonly observed in IIH with a proposed role in its pathophysiology. Methods: In this single‐center, retrospective, matched case‐control study, venous and pituitary imaging data of consecutive patients undergoing endoscopic surgery for sCSF rhinorrhea over the last 10 years were retrospectively reviewed. Measurement of the height of the pituitary gland was used to assess empty sella and VSS was quantified as the ratio between the minimal area of the transverse sinus and the cross‐sectional area of the sigmoid sinus. VSS was considered significant when it was ≥50% and bilateral. Cases were compared with 1:1 age‐ and sex‐adjusted controls explored for causes other than IIH, intracranial mass effect, or venous thrombosis. Results: Twenty‐nine patients were included (median age 56 years, females 69%, body mass index [BMI] 33.8 kg/m 2 ). Cases had a significantly lower height of the pituitary gland than controls (2.5 mm vs 6.6 mm, p < 0.001). Bilateral VSS was found in 23 of 29 cases (79%; 95% confidence interval [CI], 65% to 94%) vs 3 of 29 controls (10%; 95% CI, 0% to 21%), with p < 0.001. Conclusion: In this retrospective study, sCSF leaks were strongly associated with VSS. This novel finding provides a rationale for further investigation of the role of VSS in the onset of sCSF leaks and of the potential interest in venous stenting after the surgical repair of leaks.